Heatwave restructures marine intertidal communities across a stress gradient. Issue 5 (25th March 2023) - Whalen, Matthew A.; Starko, Samuel; Lindstrom, Sandra C.; Martone, Patrick T.
Abstract: Significant questions remain about how ecosystems that are structured by abiotic stress will be affected by climate change. Warmer temperatures are hypothesized to shift species along abiotic gradients such that distributions track changing environments where physical conditions allow. However, community‐scale impacts of extreme warming in heterogeneous landscapes are likely to be more complex. We investigated the impacts of a multiyear marine heatwave on intertidal community dynamics and zonation on a wave‐swept rocky coastline along the Central Coast of British Columbia, Canada. Leveraging an 8‐year time series with high seaweed taxonomic resolution (116 taxa) that was established 3 years prior to the heatwave, we document major shifts in zonation and abundance of populations that led to substantial reorganization at the community level. The heatwave was associated with shifts in primary production away from upper elevations through declines in seaweed cover and partial replacement by invertebrates. At low elevations, seaweed cover remained stable or recovered rapidly following decline, being balanced by increases in some species and decreases in others. These results illustrate that, rather than shifting community zonation uniformly along abiotic stress gradients, intense and lasting warming events may restructure patterns of ecological dominance and reduce total habitability of ecosystems, especially at extreme ends of pre‐existing abiotic gradients.